2020
DOI: 10.1177/2192568220925782
|View full text |Cite
|
Sign up to set email alerts
|

Prospective Randomized Controlled Trial to Study the Effect of Local Steroids in the Retropharyngeal Space After Anterior Cervical Discectomy and Fusion

Abstract: Study Design: Prospective randomized controlled trial. Objective: To study the effect of local steroids in the retropharyngeal space after anterior cervical discectomy and fusion (ACDF) in reducing prevertebral soft-tissue swelling (PSTS) and complications associated with it. Methods: A total of 50 consecutive patients operated with ACDF were double-blinded randomized into 2 groups: steroids (25) and control (25). Triamcinolone in collagen sponge was used in the steroid group and normal saline in gelatin spong… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
42
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(42 citation statements)
references
References 18 publications
0
42
0
Order By: Relevance
“…Corticosteroids can promote apoptosis of osteoblasts and bone cells, which may affect bone healing as well as increase the risk of prosthetic joints. In this meta-analysis, although some studies reported cases of postoperative pseudarthrosis, but at subsequent follow-up, there were signs of bone nonunion in both groups, while excluding the possibility of a significant effect of steroids on bone healing [15]. However, this result should be interpreted with caution, because two of the eight studies did not report infection rates and four did not report pseu-darthrosis rates.…”
Section: Discussionmentioning
confidence: 74%
See 1 more Smart Citation
“…Corticosteroids can promote apoptosis of osteoblasts and bone cells, which may affect bone healing as well as increase the risk of prosthetic joints. In this meta-analysis, although some studies reported cases of postoperative pseudarthrosis, but at subsequent follow-up, there were signs of bone nonunion in both groups, while excluding the possibility of a significant effect of steroids on bone healing [15]. However, this result should be interpreted with caution, because two of the eight studies did not report infection rates and four did not report pseu-darthrosis rates.…”
Section: Discussionmentioning
confidence: 74%
“…To compare the overall PSTS of the two groups, the mean PSTS at C3, 4, and 5 where edema was observed to be most pronounced was defined as the prevertebral soft-tissue swelling index (PSTSI). PSTSI eliminates interindividual differences, such as vertebral width or any other abnormalities in the cervical or retropharyngeal space, facilitating comparisons with other postoperative patients as well as with the patients themselves [14,15].…”
Section: Selection Of Literaturementioning
confidence: 99%
“… 14 ) However, even if thickened soft tissue in the front of the vertebral body may cause dysphagia, swallowing rarely becomes impossible. 15 ) In this case, the retropharyngeal space the day after the operation increased to 15.8 mm, so the aphagia was due to the esophageal trismus.…”
Section: Discussionmentioning
confidence: 99%
“…In total, 252 patients received intravenous steroids, 310 patients received topical steroids, and 619 patients served as controls. The corticosteroid treatment arms utilized IV dexamethasone ( 16 , 22 , 28 , 29 ) or methylprednisolone ( 31 , 33 ) or local injection of methylprednisolone ( 24 27 , 30 , 32 ) or triamcinolone ( 18 , 23 , 28 ).…”
Section: Resultsmentioning
confidence: 99%
“…Five studies reported numbers of fusion events at 1-year follow-up time and were included ( 18 , 22 , 23 , 28 , 29 ). There existed no significant difference between groups regarding fusion rate (OR = 0.87, 95% CI: 0.46–1.65), and no significant heterogeneity among these studies was found with a fixed-effect model ( I 2 = 0.0%, p = 0.999) ( Figure 6 ).…”
Section: Resultsmentioning
confidence: 99%